Task Shifting Strategy in Diabetes Control Policy: Empowering Health Cadres as Preventive Agents in Indonesia: Systematic Literature Review - Ahmad Kholid; Gipta Galih Widodo (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Diabetes Mellitus in Indonesia continues to increase with a high number of undiagnosed cases . The limited number of medical personnel encourages the implementation of the Task Shifting strategy through empowering health cadres in primary care . The research aims to review the effectiveness of Task Shifting in controlling diabetes in Indonesia, including implementation challenges and the role of digital technology . The research used the Systematic Literature Review (SLR) method according to PRISMA 2020 guidelines , literature searches were carried out on the Scopus , PubMed , Web of Science and Google Scholar databases for the period 2022–2026. From 385 journals , 22 studies were selected after quality assessment using JBI, CASP, and AMSTAR 2. The research results showed that Task Shifting was proven to be effective in increasing early detection , treatment adherence , and healthy living behavior through community-based education . The use of mHealth technology significantly help cadres in data reporting and patient assistance , while the local cultural approach increases community acceptance . Even though it is effective , the implementation of this strategy still faces obstacles in the form of limited resources , low digital literacy , and administrative burdens for cadres . In conclusion , empowering health cadres through Task Shifting is an effective and sustainable approach in supporting the transformation of primary health services and efforts to diabetes control in Indonesia.